THE IMPACT OF GREEN FINANCE, CASH FLOW, REGULATION AND PROFITABILITY ON INVESTMENT DECISIONS IN INDONESIAN MANUFACTURING COMPANIES - Muhammad Wisnu Iksantoro; Harti Budi Yanti (ZILLZELL MEDIA PRIMA, 2024)
This study aims to analyze the impact of green finance, cash flow, regulation, and profitability on investment decisions in manufacturing companies in Indonesia. This research was conducted in Manufacturing companies from 2019 to 2023 with a sample of 40 companies multiplied by 5 years so that 200 observation data obtained on the Indonesia Stock Exchange with the software used, namely EViews. The results show that green finance and regulation have no effect on investment decisions, while cash flow and profitability have a significant effect on investment decisions. This means that the better the company provides cash flow and high profitability, the better it can improve investment decisions.